TEKNIK UP SELLING DALAM MENINGKATKAN PENJUALAN DI RESTORAN RESINDA HOTEL KARAWANG - Bayu Setiawan Christian Dani; Dr. Siti Zakiah, S.Par., MM.Par (Media Bina Ilmiah, 2024)
This study examines the implementation of up selling techniques at the Resinda Hotel Karawang restaurant and their impact on increasing sales. Up selling is a sales strategy aimed at offering higher-value products or services to enhance the total transaction value. The research employs a qualitative approach with a case study design, collecting data through in-depth interviews with restaurant staff. The findings reveal that up selling techniques employed include recommending premium menu items, complete meal packages, portion upgrades, drink pairings, desserts, seasonal menus, and larger portions. These techniques are effective in boosting sales and enhancing customer experience. Success is measured through changes in total bills and customer feedback, although a major challenge is ensuring recommendations do not feel pushy. Internal factors such as staff communication skills and menu knowledge, along with external factors like special events and seasons, influence the effectiveness of these techniques. The study recommends improved training, the use of technology, regular monitoring and evaluation, focusing on customer experience, and adapting to external conditions.